Hello All,

I'm stuck on part (b)

Problem:

(a) Prove that if $\displaystyle a$ and $\displaystyle b$ are elements of an Abelian group $\displaystyle G$, with $\displaystyle \circ (a) = m$ and $\displaystyle \circ (b) = n$, then $\displaystyle (ab)^{mn} = e$ ($\displaystyle e$ denotes the identity element in my text). Indicate where you use the condition that $\displaystyle G$ is Abelian.

(b) With $\displaystyle G,~a$ and $\displaystyle b$ as in part (a), prove that $\displaystyle \circ (ab)$ divides $\displaystyle \circ (a) \circ (b)$.

(c) Give an example of an Abelian group $\displaystyle G$ and elements $\displaystyle a$ and $\displaystyle b$ in $\displaystyle G$ such that $\displaystyle \circ (ab) \ne \circ (a) \circ (b)$. Compare part (b)

Things that might come in Handy:

Let $\displaystyle G$ be a group and $\displaystyle a \in G$.

We define the order of $\displaystyle a$, denoted $\displaystyle \circ (a)$, to be the smallest, positive integer $\displaystyle n$ such that $\displaystyle a^n = e$. If no such integer exists, we say $\displaystyle a$ has infinite order.

$\displaystyle a^n$ of course means $\displaystyle a$ operating on itself $\displaystyle n$ times. that is, $\displaystyle a^n = \underbrace{aaaa \cdots a}_{n \mbox{ times}} = a*a*a*a* \cdots *a$

Tell me if you guys need anymore information.

What I have tried:

(a)Proof:Let $\displaystyle a,~b,~G$ be as in part (a). Since $\displaystyle G$ is Abelian, $\displaystyle (ab)^{mn} = a^{mn}b^{mn}$

Now, $\displaystyle a^{mn}b^{mn} = a^{mn}b^{nm} = (a^m)^n(b^n)^m = e^ne^n = ee = e$

QED

(b) This is where I'm stuck. Here's what I did so far.

Let $\displaystyle a,~b,~G$ be as in part (a). And let $\displaystyle \circ (ab) = p$.

Then $\displaystyle m,~n, \mbox{ and }p$ are all the smallest, positive integers such that: $\displaystyle a^m = e$, $\displaystyle b^n = e$ and $\displaystyle (ab)^p = a^pb^p = e$. We want to show that $\displaystyle p|mn$, that is, $\displaystyle mn = kp$ for some $\displaystyle k \in \mathbb{Z}$.

Now, $\displaystyle a^mb^n = ee = e = a^pb^p$

...

that's it, I'm not sure where to go from there. I've tried several things, but they all end up doing nothing.

(c) My example was $\displaystyle (\mathbb{Z}_3, \oplus)$ with $\displaystyle a = [1]$ and $\displaystyle b = [2]$

Thanks guys and gals